Properties and Quality of Soils and Nutrients Status of Plants on Cilacap Iron Sands Mine Sites - Yulianto, A.; Suwarno, I. (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
Iron sand deposits are widely distributed in Indonesia. They are found in costal areas of south Java, west Sumatra, South Sulawesi and north of West Irian Islands. Deposit of iron sand on south coast of Cilacap Regency, Central Java Province is the first iron sand deposit exploited by PT Antam Tbk, a state mining enterprise. Mining of iron sands in this area was started in 1970 and closed in 2003. In contrast with other post mining lands, most iron sand post mining lands in Cilacap (60%) were utilized as agricultural lands (PT Antam Tbk, 2005). Mining of iron sands at Cilacap iron sand mine site (ISMS) was carried out by open pit mining with hydraulic mining and back-filling systems. This mining method disturbs chemical, physical and biological properties of soil, which in turn causes soil and environmental degradation. Soil degradation of post mining lands includes: concentrating elements potentially toxic to plants; concentrating heavy metal hazardous to human; or degradation of the chemical, physical and biological properties of soils. Because soil is plant growth medium, soil degradation of post mining lands affects plants grown on this soil. On heavily degraded soils of post mining lands, the growth of plants may be restricted; or plants may grow well, but their products are harmful for human health to be consumed.